2006
DOI: 10.1007/s10800-005-9105-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cr(III) solution chemistry on electrodeposition of chromium

Abstract: This work provides a new insight into the interaction of urea with formate during the chromium electrodeposition from a sulphate-based Cr(III) solution. The influence of solution chemistry on chromium electrodeposition in a Cr(III) bath containing sodium formate and urea as complexing agents was studied by FT-IR, XPS and AFM. The results show that good quality Cr coatings may be obtained only in those cases when the secondary ligand with the carbamidic group predominates over urea in the electrolyte. This sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(29 citation statements)
references
References 11 publications
3
24
0
2
Order By: Relevance
“…have been investigated as a complexing agent for Cr 3+ ions to improve the current efficiency for Cr deposition. Furthermore, N-containing compounds such as glycine [10], urea [11][12][13], thiocyanate [14], etc. have been also investigated to improve the surface appearance of Cr deposits.…”
Section: +mentioning
confidence: 99%
“…have been investigated as a complexing agent for Cr 3+ ions to improve the current efficiency for Cr deposition. Furthermore, N-containing compounds such as glycine [10], urea [11][12][13], thiocyanate [14], etc. have been also investigated to improve the surface appearance of Cr deposits.…”
Section: +mentioning
confidence: 99%
“…Baral [8], Baosong [10] and Survilliene [9,11] have studied the effect of the operating conditions such as the pH, temperature, current density and adding agents on the cathodic efficiency, morphology and structure of deposits, obtaining a response variable dependence in all cases.…”
Section: +3mentioning
confidence: 99%
“…It can be seen that oxygen was incorporated into all samples, perhaps in the form of an oxide or hydroxide due to the pH increase in the cathode during the electrode reaction. Phosphorus was also incorporated to the coatings when hypophosphite was added to the solution, as found by XPS analysis in [9][10][11]. On the other hand, aluminum was not detected by EDX measurements in coatings obtained from solutions containing AlCl 3 .…”
Section: Uv-visible Spectramentioning
confidence: 99%
“…It has been shown that problems in syn thesis of thick Cr deposits from Cr(III) solutions are primarily due to the processes of hydrolysis of the elec trolyte components in the near electrode layer and further inclusion of low soluble hydroxy compounds of chromium into the deposit [12,13]. Therefore, a correct choice of the nature and concentration of organic additives (ligands, buffers, water-soluble polymers) allowing providing the optimum state of the near electrode layer in the process of chromium plat ing and suppressing hydroxide formation is of funda mental importance [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoc rystalline chromium-carbon alloys were deposited from these electrolytes at a rather high current effi ciency, reaching 30% or more (at a deposition rate of 1-1.5 µm/min or more) [3,4,17,18,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%